Review of Research on Vehicles Aerodynamic Drag Reduction Methods - Sudin, Mohd Nizam; ABDULLAH, Mohd Azman; Ramli, Faiz Redza; Musthafah, Mohd Tahir; Shamsudin, Shamsul Anuar (IJENS Publishers, 2014)
Recent spikes in fuel prices and concern regarding greenhouse gas emissions, automotive design engineers are faced with the immediate task of introducing more efficient aerodynamic designs vehicles. The aerodynamic drags of a road vehicle is responsible for a large part of the vehicle’s fuel consumption and contribute up to 50% of the total vehicle fuel consumption at highway speeds. Review on the research performance of active and passive flow control on the vehicle aerodynamic drag reduction is reported in this paper. This review intends to provide information on the current approaches and their efficiency in reducing pressure drag of ground vehicles. The review mainly focuses on the methods employed to prevent or delay air flow separation at the rear end of vehicle. Researches carried out by a number of researchers with regard to active and passive flow controls method on vehicle and their effect on aerodynamic drag in terms of drag coefficient (CD) was highlighted. Passive methods i.e. Vortex Generator (VG), spoiler and splitter and active flow controls i.e. steady blowing, suction and air jet are among the methods had been reviewed. In addition several attempts to couple these flow control methods were also reviewed. Several aspects of aerodynamic drag that need for further investigation as to assist for vehicles aerodynamic design and for practical reasons were highlighted. Progressive research on active flow control was observed due to its flexibility for wide range of application without body shape modification.